Long term outcome after transjugular intrahepatic portosystemic stent-shunt in non-transplant cirrhotics with hepatorenal syndrome: a phase II study. Issue 2 (1st August 2000) - Brensing, K A; Textor, J; Perz, J; Schiedermaier, P; Raab, P; Strunk, H; Klehr, H U; Kramer, H J; Spengler, U; Schild, H; Sauerbruch, T
Abstract : BACKGROUND: Recent small studies on hepatorenal syndrome (HRS) indicate some clinical benefit after transjugular intrahepatic portosystemic stent-shunt (TIPS) but sufficient long term data are lacking. AIM: We studied prospectively feasibility, safety, and long term survival after TIPS in 41 non-transplantable cirrhotics with HRS (phase II study). PATIENTS AND METHODS: HRS was diagnosed using current criteria (severe (type I) HRS, n=21; moderate (type II) HRS, n=20). Thirty one patients (14 type I, 17 type II) received TIPS (8–10 mm) while advanced liver failure excluded shunting in 10. During follow up (median 24 months) we analysed renal function and survival (Kaplan-Meier). RESULTS: TIPS markedly reduced the portal pressure gradient (21 (5) to 13 (4) mm Hg (mean (SD)); p<0.001) with one procedure related death (3.2%). Renal function deteriorated without TIPS but improved (p<0.001) within two weeks after TIPS (creatinine clearance 18 (15) to 48 (42) ml/min; sodium excretion 9 (16) to 77 (78) mmol/24 hours) and stabilised thereafter. Following TIPS, three, six, 12, and 18 month survival rates were 81%, 71%, 48%, and 35%, respectively. As only 10% of non-shunted patients survived three months, total survival rates were 63%, 56%, 39%, and 29%, respectively. Multivariate Cox regression analysis revealed bilirubin (p<0.001) and HRS type (p<0.05) as independent survival predictors after TIPS. CONCLUSIONS: TIPS provides long term renal function and probably survival benefits in the majority of non-transplantable cirrhotics with HRS. These data warrant controlled trials evaluating TIPS in the management of HRS.